Which Firms Create the Most Jobs in Developing Countries? Evidence from Tunisia - Rijkers, Bob; Arouri, Hassen; Freund, Caroline; Nucifora, Antonio (World Bank Group, Washington, DC, 2014)
This paper examines private sector job creation in Tunisia over the period 1996-2010 using a unique database containing information on all registered private enterprises, including self-employment. In spite of stable growth of gross domestic product, overall net job creation was disappointing and firm dynamics were sluggish. The firm size distribution has remained skewed toward small firms, because of stagnation of incumbents and entrants starting small, typically as one-person firms (self-employment). Churning is limited, especially among large firms, and few firms manage to grow. Post-entry, small firms are the worst performers for job creation, even if they survive. Moreover, the association between productivity, profitability, and job creation is feeble, pointing towards weaknesses in the re-allocative process. Weak net job creation thus appears to be due to insufficient firm dynamism rather than excessive job destruction.